ANALISIS PERAN MEDIA DALAM MENUMBUHKAN KESADARAN BELA NEGARA PADA GENERASI MILENIAL 4.0 - Hery Yuniarto (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Currently, Indonesia has entered the 4.0 era where changes in everything are related to digitalization. Media is the most important medium in the millennial generation. The development of media in Indonesia is currently increasing drastically. Based on the results of the data obtained from the databoks (2021) it shows that the millennial 4.0 generation of youth accesses the internet more. The time spent by the millennial generation on social media is the application that is accessed the longest by the millennial 4.0 generation, which is 2.5 hours per day, on streaming services for 1.7 hours, reading articles on online media for 1.4 hours and listening to podcasts for 1 hour. ,1 hour. In the millennial generation the threat received is not a military threat, but a more complex threat than that is a non-military threat that is able to erode the sense of nationalism of the nation's future millennial generation. utilizing new media to raise awareness of the Millennial generation. One example is the publication of news in online media entitled Atta Halilintar, sharing the moment when he was appointed as an ambassador for the country's defense.